Development of Gamification-Based Learning Media on Atmospheric Dynamics Material - Fitria, Ade; Azis, Daska; Desfandi, Mirza; Gadeng, Ahmad Nubli (Tunas Geografi, 2025)
This development research aims to produce a gamification-based learning media that is feasible and effective for teaching the topic of atmospheric dynamics and its impact on life in Geography subjects. The material on atmospheric dynamics and its impacts includes several subtopics, namely: (1) identifying the layers of the Earth's atmosphere, (2) analyzing weather elements and interpreting weather data, (3) identifying atmospheric dynamics and their impact on life, (4) analyzing the classification of climate types and global climate patterns, and (5) understanding the characteristics of Indonesia's climate and its influence on human activities. This research explains that gamification does not mean creating a game, but rather developing specialized media to apply gamification concepts more effectively. The development of the media was carried out using the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This study produced learning media containing gamification elements such as points, badges, challenges, competition, collaboration, levels, content unlocking, duration, tasks, and game rules. The model used in the implementation of this gamification-based learning media is the Game-Based Learning model. Data collection techniques in this research used questionnaires with a Likert scale. The results obtained showed a validation score from media experts of 89%, from material experts of 83%, and students' trial results reached 83% as well. Therefore, the gamification-based learning media is categorized as “highly feasible” for use.